Effect of Ni addition on the arc-erosion behavior of AgTiB2 contact material. (March 2019) - Li, Hangyu; Wang, Xianhui; Xi, Yong; Zhu, Ting; Guo, Xiuhua
Abstract: To disclose the electrical characteristics of AgTiB2 contact materials with different Ni additions, the arc-erosion tests were performed 20, 000 times at 24 V/16 A DC. The morphology and chemical composition of arc eroded contact surface were characterized by scanning electron microscopy and energy dispersive X-ray spectrometry, the mass change after arc-erosion tests was determined, the arc energy and arc duration at make-arc and break-arc were analyzed, and the arc erosion mechanism was discussed as well. The results show that arc erosion mode changes from anodic erosion to cathodic erosion with Ni addition. The Ag-4 wt.%TiB2 contact material with 2 wt%Ni addition has the optimum performance along with the least mass loss, while especially high arc energy and total mass loss generate at 4 wt% and 8 wt%Ni. Furthermore, the arc erosion mechanism was discussed based on the contact characterization, thermal property and ionization energy of materials. It is believed that excessive Ni addition is not beneficial for the improvement of arc erosion resistance since Ni has large potential to be ionized and the possibility to evaporate due to its little difference of enthalpy change compared with ionization energy. Highlights: Effect of Ni addition on arc erosion behavior of AgTiB2 contact material is disclosed. Ag-4 wt.%TiB2 material with 2 wt%Ni addition presents the best arc erosion performance along with the least mass loss. Excessive Ni addition results in large fluctuation of make-arc-energy and break-arc-energy. Arc erosion mechanism is clarified based on the thermal property and ionization energy of materials. Ionization energy has the significant effect on the arc erosion since it influences the arc stability.